A orientação profissional na perspectiva sócio-histórica: uma possibilidade para as classes pobres - Mendonça, Larissa Brito (2021)
Through the articulation of Career Guidance (CG) with the social-historical approach, it was proposed to raise and analyze this modality of intervention for the poor classes, paying attention to the possibilities and limitations both in the experience itself and in the awareness of this concrete reality for working youth, as well as the assumptions of social transformation sustained by political emancipation. Theoretical issues were covered that would provide a basis for critical understanding raised from the rise of Psychology, linked to capitalism, to the current scenario of youth. To gather data and exercise it on today's youth about work, a survey was carried out and, after that, an analysis of articles on the subject. For this, it was necessary to search for national articles on CG procedures for public schools or low-income people. Then, by analyzing them through critical criticism, the articles showed that the proposals guided by the social-historical approach conceives the career guidance as a means of raising awareness about the determinants of professional choice, discuss the dichotomization between individual and society and focus on the elaboration of the life project. A preoccupation present in the experiences was to face the concepts of neoliberal ideology that are sought in individualistic beliefs about professional choice or life projects. However, it also exposes gaps that raise concerns about acting. It was noticed that the intervention did not detail or data on the reality of Brazilian working youth. The CG in the social-historical approach may be contributing to the capture of subjectivity by raising resources to adapt to the world of work. For that added follow-ups after the interventions to observe how their contributions to the awareness of the world of work and the long-term functionality of this performance. It was possible to conclude that this intervention implies limitations that need to be understood and transformed, and that this is a means that can contribute to working youth, but immediately. It does not show itself as a means of revolutionary transformation, but it presents tendencies towards political transformations.